2011
DOI: 10.1093/nar/gkr849
|View full text |Cite
|
Sign up to set email alerts
|

Yin Yang 1 contains G-quadruplex structures in its promoter and 5′-UTR and its expression is modulated by G4 resolvase 1

Abstract: Yin Yang 1 (YY1) is a multifunctional protein with regulatory potential in tumorigenesis. Ample studies demonstrated the activities of YY1 in regulating gene expression and mediating differential protein modifications. However, the mechanisms underlying YY1 gene expression are relatively understudied. G-quadruplexes (G4s) are four-stranded structures or motifs formed by guanine-rich DNA or RNA domains. The presence of G4 structures in a gene promoter or the 5′-UTR of its mRNA can markedly affect its expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 79 publications
4
82
0
Order By: Relevance
“…The fact that many cells can readily take up G4DNA indicates that this mechanism may also allow the cell to respond to its external environment as well as internal stress (67,72). Although our results suggest important roles for G4DNA in the regulation of cytoplasmic cellular processes, other studies have suggested roles for G4DNA in modulating transcription through the binding of helicases such as DHX36 (30,96,97), the RecQ family helicases (98,99), and the XPB and XPD helicases (75). It is possible that any G4DNA-binding protein may be regulated by freely diffusing G4DNA, leading to various cellular responses based on the large number of proteins that are reported to have G4DNA binding capacity (4, 100 -102).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The fact that many cells can readily take up G4DNA indicates that this mechanism may also allow the cell to respond to its external environment as well as internal stress (67,72). Although our results suggest important roles for G4DNA in the regulation of cytoplasmic cellular processes, other studies have suggested roles for G4DNA in modulating transcription through the binding of helicases such as DHX36 (30,96,97), the RecQ family helicases (98,99), and the XPB and XPD helicases (75). It is possible that any G4DNA-binding protein may be regulated by freely diffusing G4DNA, leading to various cellular responses based on the large number of proteins that are reported to have G4DNA binding capacity (4, 100 -102).…”
Section: Discussionmentioning
confidence: 58%
“…2I) were also found in stress granules induced by G4DNA. The fraction of stress granule protein foci that contain G4DNA foci was determined to be 90,7,75,96,17, and 83% of the TIA1, DHX36, YB-1, ELAV1, G3BP, and eIF3 foci, respectively. The fraction of DHX36 and G3BP foci containing G4DNA was significantly lower than the other stress granule proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Although the structural and biophysical characterization of G-quadruplexes has progressed rapidly, the mechanistic basis for their recognition and remodeling is poorly understood. RHAU has emerged as a primary quadruplex resolvase in eukaryotic cells, and the functional consequences of quadruplex remodeling has been established in a small number of important processes (17,18,21,41,42). Therefore, our goal was to make biophysical inroads to the process by examining the recognition of G-quadruplexes by the N-terminal region of RHAU that contains the RSM, a required region for quadruplex recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray studies have implicated RHAU in broad spectrum transcriptional regulation and mRNA stability (20). In support, RHAU has been shown to control gene expression through direct binding to quadruplexes within the promoter of the YY1 gene (21). RHAU can also modulate quadruplex structures in the context of non-coding RNAs.…”
mentioning
confidence: 99%
“…RHAU and G4R1) is of particular interest for general G4 disruption activity because it is highly expressed, comprises the bulk of the DNA G4 disruption activity in a human cell lysate, and is one of only two helicases known to disrupt RNA G4s (14)(15)(16). DHX36 has been implicated as a regulator of RNA folding and assembly (17,18), RNA localization, translation (19), pre-mRNA processing (20), and transcription (21), most simply suggesting that it functions in both the cytoplasm and nucleus and interacts with both RNA and DNA G4s. Underscoring the importance of this protein and potentially G4s in vivo, DHX36 is an essential gene in mouse (22)(23)(24).…”
Section: ___________________________________mentioning
confidence: 99%